2009 IEEE Bucharest PowerTech 2009
DOI: 10.1109/ptc.2009.5281790
|View full text |Cite
|
Sign up to set email alerts
|

Virtual synchronous generator: Laboratory scale results and field demonstration

Abstract: This paper describes an approach to demonstrate the operation of virtual synchronous generators (VSG) in practical distribution systems. After an extensive simulation phase at laboratory scale, the field demonstration is planned at two sites located in the Netherlands and in Romania, for small VSGs of 10x5 kW and one large VSG of 100 kW respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Since the fundamental concept of VSMs was formally introduced, it has been subject of several publications. Most of the research deals with specific issues on the implementation of VSMs such as: the necessary requirements of the PEI to perform a VSM [3], selection of the storage media [4], laboratory prototypes for experimental tests [5] and an optimal virtual inertia controller for wind generator [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the fundamental concept of VSMs was formally introduced, it has been subject of several publications. Most of the research deals with specific issues on the implementation of VSMs such as: the necessary requirements of the PEI to perform a VSM [3], selection of the storage media [4], laboratory prototypes for experimental tests [5] and an optimal virtual inertia controller for wind generator [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the inverter behaves as a current-controlled voltage source inverter [13,48]. This topology is used by the European VSYNC research group [45,50] and has demonstrated the effectiveness of inertia emulation using VSG topology through real-time simulations [51] and several field tests [52]. In [22], an experimental verification of the topology is presented for remote microgrid applications.…”
Section: Virtual Synchronous Generators: a Frequency-power Response Bmentioning
confidence: 99%
“…The provision of emulated inertia from power electronics interfaced storage and generation has gained attention in recent years, through for example virtual synchronous machine-type controls [12,13] of the power electronics converters. Providing an inertial response typically requires short-term energy storage, and it has been investigated for energy storage systems (ESS) such as batteries, supercapacitors, and flywheel storage in [14][15][16][17][18][19] and for photo-voltaic systems operating off their maximum power point [20]. For wind turbines, the stored kinetic energy in the turbine rotor can be used in combination with VSMcontrol, as shown in [21][22][23].…”
Section: Introductionmentioning
confidence: 99%